NAP (davunetide) protects primary hippocampus culture by modulating expression profile of antioxidant genes during limiting oxygen conditions. (April 2015) - Arya, A.; Meena, R.; Sethy, N. K.; Das, M.; Sharma, M.; Bhargava, K.
Abstract Hypoxia is a well-known threat to neuronal cells and triggers the pathophysiological syndromes in extreme environments such as high altitudes and traumatic conditions such as stroke. Among several prophylactic molecules proven suitable for ameliorating free radical damage, NAP (an octapeptide with initial amino acids: asparagine/N, alanine/A, and proline/P) can be considered superlative, primarily due to its high permeability into brain through blood–brain barrier and observed activity at femtomolar concentrations. Several mechanisms of action of NAP have been hypothesized for its protective role during hypoxia, yet any distinct mechanism is unknown. Oxidative stress is advocated as the leading event in hypoxia; we, therefore, investigated the regulation of key antioxidant genes to understand the regulatory role of NAP in providing neuroprotection. Primary neuronal culture of rat was subjected to cellular hypoxia by limiting the oxygen concentration to 0.5% for 72 h and observing the prophylactic efficacies of 15fM NAP by conventional cell death assays using flow cytometry. We performed real-time quantitative polymerase chain reaction to comprehend the regulatory mechanism. Further, we validated the significantly regulated candidates by enzyme assays and immunoblotting. In the present study, we report that NAP regulates a major clad of cellular antioxidants and there is an involvement of more than one route of action in neuroprotection during hypoxia.